Er,Cr:YSGG Laser Therapy for Drug-Induced Gingival Overgrowth: A Report of Two Case Series - Liu, Yumei; Peng, Qian; Liu, Binjie; Wang, Zhibin; Cao, Qiong (Frontiers in Surgery, 2022)
Background Drug-induced gingival overgrowth is common but neglected in patients with systemic disease medications until it seriously affects the quality of life. Methods Initial periodontal treatment, combined with water laser surgery, was performed sequentially in two cases. Results The therapeutic effect was good, and there was no recurrence along with good oral hygiene. Conclusion Water laser equipment surgery, as well as initial periodontal treatment, required that surgeons are trained specifically. A tool was devised for various oral diseases, and it was safer, more efficient and more comfortable than others.